STATISTICAL ESTIMATION OF THE COMPRESSIBITY OF BAGHDAD COHESIVE SOIL (Journal of Engineering, 2024)
Because of the time and expense involved in performing consolidation tests, it is often desirable to obtain approximate values of (C, and C,) by using other soil properties which are more easily determined. The literature contains numerous equations linking soil compressibility to its physical and index properlies. As these equations are often used to obtain preliminary evaluations of (C) and (C,), it is important to know the reliability of these equations.In this paper an attempt was made to estimate (C, and C.) of Baghdad cohesive soil from other soil properties. A number of commonly used empirical correlation equations that have been developed during the last six decades to estimate (C, and C,) were compiled and evaluated. The results of routine laboratory tests of a large number of databases of Baghdad soil were correlated with more sophisticated laboratory consolidation results by conducting simple and multiple regression analyses. It was concluded that the compression index of Baghdad cohesive soil cannot be estimated from Atterberg limits and the better values of compression and recompression indices of Baghdad soil can be obtained when more than one index property is used in the regression analysis.